Sulfur Fixation by Chemically Modified Red Mud Samples Containing Inorganic Additives: A Parametric Study - Yang Liu; Yang Li; Feng-shan Zhou; Ying-mo Hu; Yi-he Zhang (Advances in Materials Science and Engineering)
Sulfur retention ability of Bayer red mud from alumina plant was investigated. Bayer red mud modified by fusel salt and waste mother liquor of sodium ferrocyanide as the main sulfur fixation agent and the calcium based natural mineral materials as servicing additives; the experimental results showed the following: (1) Through 10 wt% waste mother liquor of sodium ferrocyanide modifying Bayer red mud, sulfur fixation rate can increase by 13 wt%. (2) Magnesium oxide can obviously improve the sulfur fixation performance of Bayer red mud and up to a maximum sulfur fixation rate of 47 wt% at adding 1 wt% magnesium oxide. (3) Dolomite enhanced the sulfur fixation performances with the sulfur fixation rate of 68 wt% in optimized condition. (4) Vermiculite dust reduced sulfur dioxide during the fixed-sulfur process of modified Bayer red mud, and the desulphurization ration could reach up to a maximum 76 wt% at 950°C. (5) An advanced three-component sulfur fixation agent was investigated, in which the optimized mass ratio of modified Bayer red mud, dolomite, and vermiculite dust was 70 : 28 : 2 in order, and its sulfur fixation efficiency has reached to a maximum 87 wt% under its 20 wt% dosage in the coal.